NAFTA and the Politics of Labor Transnationalism, by Tamara Kay (Meridiano 47 - Journal of Global Studies, 2017)
Reserha de KAY, Tamara. NAFTA and the Politics of Labor Transnationalism. 1a. edição, Nova Iorque: Cambridge University Press, 2011, 310 p. ISBN 978-0-521-13295-4.